Survival Advantage Following TAG-72 Antigen-Directed Cancer Surgery in Patients With Colorectal Carcinoma: Proposed Mechanisms of Action - Hitchcock, Charles L.; Povoski, Stephen P.; Mojzisik, Cathy M.; Martin, Edward W. (Frontiers in Oncology, 2021)
Patients with colorectal carcinoma continue to have variable clinical outcomes despite undergoing the same surgical procedure with curative intent and having the same pathologic and clinical stage. This problem suggests the need for better techniques to assess the extent of disease during surgery. We began to address this problem 35 years ago by injecting patients having either primary or recurrent colorectal carcinoma, with 125I-labeled murine monoclonal antibodies against the tumor-associated glycoprotein-72 (TAG-72) and using a handheld gamma-detecting probe (HGDP) for intraoperative detection and removal of radioactive, i.e., TAG-72 positive, tissue. Data from these studies demonstrated a significant difference in overall survival data (p < 0.005 or better) when no TAG-72 positive tissue remained compared to when TAG-72 positive tissue remained at the completion of surgery. Recent publications indicate that aberrant glycosylation of mucins and their critical role in suppressing tumor-associated immune response help explain our results' underlying cellular mechanisms. We propose that monoclonal antibodies to TAG-72 recognize and bind to antigenic epitopes on mucins that suppress the tumor-associated immune response (TAIR) in both the tumor and tumor-draining lymph nodes. Complete surgical removal of all TAG-72 positive tissue serves to reverse the escape phase of immunoediting, allowing a resetting of the TAIR that leads to the improved overall survival of the patients with either primary or recurrent colorectal carcinoma. Thus, the status of TAG-72 positivity after resection has a significant impact on patient survival.